2016
DOI: 10.1111/bcp.13126
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule destabilising agents: far more than just antimitotic anticancer drugs

Abstract: Vinca alkaloids have been approved as anticancer drugs for more than 50 years. They have been classified as cytotoxic chemotherapy drugs that act during cellular mitosis, enabling them to target fast growing cancer cells. With the evolution of cancer drug development there has been a shift towards new "targeted" therapies to avoid the side effects and general toxicities of "cytotoxic chemotherapies" such as the vinca alkaloids. Due to their original classification, many have overlooked the fact that vinca alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
213
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(226 citation statements)
references
References 96 publications
2
213
0
1
Order By: Relevance
“…Other researchers are designing cathepsin D (CDSD) inhibitors for the treatment of breast cancer . Also, there are successful anticancer drugs designed whose mechanism is explained by their ability to disrupt microtubules and so halt cell cycle and induce apoptosis . Thus, detected protein changes in AML patients’ blasts are advantageous for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers are designing cathepsin D (CDSD) inhibitors for the treatment of breast cancer . Also, there are successful anticancer drugs designed whose mechanism is explained by their ability to disrupt microtubules and so halt cell cycle and induce apoptosis . Thus, detected protein changes in AML patients’ blasts are advantageous for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Particular MTAs cause cell cycle arrest during G2/M phase, activating the apoptotic signalling pathway in tumour cells [2.3]. Additionally, MTAs have been shown to affect cells in interphase (G1) . Thus, the suppression of microtubule dynamics without the accumulation of mitotic cells also induces apoptosis of cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MTAs have been shown to affect cells in interphase (G1) . Thus, the suppression of microtubule dynamics without the accumulation of mitotic cells also induces apoptosis of cancer cells . Previous studies have suggested that MTAs exert their cytotoxic effects by altering mitochondrial function and cellular signalling, which is independent of the cell cycle .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Microtubules (MTs), key protein filaments of the cytoskeleton, are constructed by the regular arrangement of globular a/b-tubulin heterodimers in ah ighly dynamic manner. [5] Further to some known naturalproduct MT stabilizing/destabilizing agents (for example, paclitaxel and vinca alkaloids), [6] tubulin-targeted antimitotic peptides have become alternative or even prime candidates for innovative drug discovery and development, mainly due to their immense advantages in avoiding the general cytotoxicity and multidrug resistance of conventional chemotherapeutic compounds. [5] Further to some known naturalproduct MT stabilizing/destabilizing agents (for example, paclitaxel and vinca alkaloids), [6] tubulin-targeted antimitotic peptides have become alternative or even prime candidates for innovative drug discovery and development, mainly due to their immense advantages in avoiding the general cytotoxicity and multidrug resistance of conventional chemotherapeutic compounds.…”
mentioning
confidence: 99%